Dynamics, nanomechanics and signal transduction in reelin repeats - Mikulska-Ruminska, Karolina (Sci Rep, 2019)
Reelin is a large glycoprotein controlling brain development and cell adhesion. It regulates the positioning of neurons, as well as neurotransmission and memory formation. Perturbations in reelin signaling are linked to psychiatric disorders. Reelin participates in signal transduction by binding to the lipoprotein receptors VLDLR and ApoER2 through its central region. This part is rich in repeating BNR-EGF-BNR modules. We used standard molecular dynamics, steered molecular dynamics, and perturbation response scanning computational methods to characterize unique dynamical properties of reelin modules involved in signaling. Each module has specific sensors and effectors arranged in a similar topology. In the modules studied, disulfide bridges play a protective role, probably making both selective binding and protease activity of reelin possible. Results of single reelin molecule stretching by atomic force microscopy provide the first data on the mechanical stability of individual reelin domains. The forces required for partial unfolding of the modules studied are below 60 pN.